Efeitos do fortalecimento muscular do quadril e tronco sobre a cinemática dapelve e do quadril na marcha considerando a influência do alinhamento do complexo tornozelo-pé - Aline de Castro Cruz (2017)
Introduction: After performing a program of strengthening of the hip and trunk, individuals with different levels of foot-ankle complex (FAC) varism may present different kinematic effects on the pelvis and hip during gait, which could influence the effects on hip torques. Therefore, the objective of this study was to evaluate the effects of hip and trunk strengthening on the kinematics of the pelvis and hip during gait and on the passive and active properties of the hip, and to verify if the magnitude of these effects is influenced by the varism level of the FAC. Methods: A study wasconducted with 53 healthy women divided into control and intervention groups. Both groups were divided into subgroups, with higher and lower varism values. The intervention group (n = 26; 22±3 years) performed muscle strengthening of the hip and trunk. The control group (n = 27; 21±1 years) was instructed to maintain their usual activities. The kinematic variables (1) and the passive (2) and active (3) hip properties evaluated before and after strengthening were: (1) ranges of pelvicanterior rotation and lateral drop, hip medial rotation and adduction, (2) the mean passive lateral torque of the hip and the passive range of medial rotation of the hip and (3) the peak of concentric and eccentric torques of the lateral rotators of the hip. Results: There were no significant differences between the intervention and control groups for the hip and pelvic ranges. However, the subgroup of women with lower values of varism, of the intervention group, presented reduction of pelvic drop after strengthening (p = 0.033), which was not observed for the subgroup with higher values (p = 0.057) and for both control subgroups (p = 0.703 and p = 0.806). In addition, the subgroup of the intervention with lower values of varism presented a significant reduction of passive range of medial rotation of the hip after strengthening (p = 0.012). The subgroup of individuals in the control group with higher values of varism presented an increase in passive amplitude of medial hip rotation (p = 0.007) after the eight week period, which did not occur with the control subgroup with lower values of varism (p = 0.242). The intervention group increased the passive torque (p = 0.001), the concentric and eccentric torque peak of the lateral rotators (p <0.001 for both) after the hip and trunk muscle strengthening program, which was not observed for the control group. The effects of strengthening on active and passive hip torques were not dependent on the varism. Conclusion: The strengthening of the hip and trunk modified the kinematics of the pelvis in gait (frontal plane), and increased hip torques. Women with lower values of varism presented reduction of the pelvic drop during a gait and reduction of the passive amplitude of medial hip rotation after the strengthening. Thus, the level varism influenced the effects of strengthening on the kinematics of the pelvis and on the passive properties of the hip.